On the Roles and Rationales of European STI Policies - Rahel Falk; Werner Hölzl; Hannes Leo (Austrian Institute of Economic Research (WIFO), 2007)
EU enlargement has increased the diversity of the European Union in a substantial way, in particular with respect to its capacities in the fields of science, technology and innovation (STI). The shares of both gross and business sector expenditures on R&D in GDP are increasingly diverging following EU enlargement, pointing at quite different levels of technological opportunities and absorptive capacity. Against this background, this paper tries to disentangle the rationales for STI policies at an EU level. Starting from the different policy rationales we assign different STI policy fields to levels of governance. Our discussion suggests that the European Union plays two quite distinct roles in EU STI policy. The first role is closely related to the assignment of policy competences and establishes the fields where the EU should act as policy maker and programme owner. But this alone is likely to be insufficient when it comes to managing and coordination of complex horizontal policy fields such as STI policy. Here the second role of the European Commission comes into its own. This second role is not related to policy making but to the "right" to fuel discussions to find coordinated solutions. This role is essentially political and relates to the job to stimulate activities in areas where the Commission has no mandate (due to missing clear rationales) to act alone.
Keywords: 330; EU enlargement; science; technology and innovation (STI); policy rationales; subsidiarity; policy competences; coordination; horizontal policy fields; Technologiepolitik; Technologiepolitik; Politische Entscheidung; Governance-Ansatz; EU-Staaten